2023
DOI: 10.3762/bjoc.19.73
|View full text |Cite
|
Sign up to set email alerts
|

The unique reactivity of 5,6-unsubstituted 1,4-dihydropyridine in the Huisgen 1,4-diploar cycloaddition and formal [2 + 2] cycloaddition

Abstract: The three-component reaction of isoquinolines, dialkyl acetylenedicarboxylates, and 5,6-unsubstituted 1,4-dihydropyridines in acetonitrile at room temperature afforded functionalized isoquinolino[1,2-f][1,6]naphthyridines in good yields and with high diastereoselectivity. More importantly, the formal [2 + 2] cycloaddition reaction of dialkyl acetylenedicarboxylates and 5,6-unsubstituted 1,4-dihydropyridines in refluxing acetonitrile gave unique 2-azabicyclo[4.2.0]octa-3,7-dienes as major products and 1,3a,4,6a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In recent years, 5,6-unsubstituted 1,4-dihydropyridines have been recognized as the reactive electron-rich dienophiles, which proceeded several Povarov reactions with various 1-aza-1,3-butadienes [ 40 44 ]. Recently, we have found that the three-component reaction of isoquinolines, dialkyl but-2-ynediaotes and 5,6-unsubstituted 1,4-dihydropyridines afforded functionalized isoquinolino[1,2- f ][1,6]naphthyridines in good yields and with high diastereoselectivity via a [4 + 2] cycloaddition process [ 45 ]. Very recently, we also found that base-promoted [4 + 2] cycloaddition of salicyl N -tosylimines and 5,6-unsubstituted 1,4-dihydropyridines resulted in novel tetrahydrochromeno[3,2- b ]pyridine derivatives in satisfactory yields [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 5,6-unsubstituted 1,4-dihydropyridines have been recognized as the reactive electron-rich dienophiles, which proceeded several Povarov reactions with various 1-aza-1,3-butadienes [ 40 44 ]. Recently, we have found that the three-component reaction of isoquinolines, dialkyl but-2-ynediaotes and 5,6-unsubstituted 1,4-dihydropyridines afforded functionalized isoquinolino[1,2- f ][1,6]naphthyridines in good yields and with high diastereoselectivity via a [4 + 2] cycloaddition process [ 45 ]. Very recently, we also found that base-promoted [4 + 2] cycloaddition of salicyl N -tosylimines and 5,6-unsubstituted 1,4-dihydropyridines resulted in novel tetrahydrochromeno[3,2- b ]pyridine derivatives in satisfactory yields [ 46 ].…”
Section: Introductionmentioning
confidence: 99%